2015
DOI: 10.1111/all.12663
|View full text |Cite
|
Sign up to set email alerts
|

CYT003, a TLR9 agonist, in persistent allergic asthma – a randomized placebo‐controlled Phase 2b study

Abstract: Toll-like receptor-9 agonism with CYT003 showed no additional benefit in patients with insufficiently controlled moderate-to-severe allergic asthma receiving standard inhaled glucocorticosteroid therapy with or without LABAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…However, the role of TLR9 as a novel therapeutic target for allergic airway disease is still controversial. Synthetic TLR9 ligands (CpG ODNs) are shown to be beneficial in various animal models of asthma and even in a number of early human clinical trials , while CpG ODNs are also reported to activate TLR9 and cause lung inflammation . In fact, consistent with our previous report and the study of Carmen Maldonado‐Berna that high expression of TLR9 is found in asthma , the present study demonstrated that pronounced elevated expression of TLR9 was accompanying with lung inflammation exacerbation in WT mice after OVA challenges.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the role of TLR9 as a novel therapeutic target for allergic airway disease is still controversial. Synthetic TLR9 ligands (CpG ODNs) are shown to be beneficial in various animal models of asthma and even in a number of early human clinical trials , while CpG ODNs are also reported to activate TLR9 and cause lung inflammation . In fact, consistent with our previous report and the study of Carmen Maldonado‐Berna that high expression of TLR9 is found in asthma , the present study demonstrated that pronounced elevated expression of TLR9 was accompanying with lung inflammation exacerbation in WT mice after OVA challenges.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, modulators have been developed to target TLRs for the therapeutic potential, with a particular focus on TLR9. CpG oligodeoxynucleotides, which are TLR9 ligands, have been used in the treatment of allergic airway diseases such as asthma in animal models and even in placebo‐controlled phase II study . Nevertheless, achieving inflammation control is still an important goal in the management of allergic airway disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, just recently, there was a report that administration of this same Qβ-derived nanoparticle complex resulted in no therapeutic improvement in patients with persistent moderate-to-severe allergic asthma. 99 Therefore, the efficacy of this particular nanomedicine may only apply to patients with controlled mild-to-moderate persistent allergic asthma undergoing glucocorticosteroid withdrawal.…”
mentioning
confidence: 99%
“…We included the well-known Qβ VLP-based allergy vaccine CYT003-QbG10 that contains an encapsulated CpG sequence, so-called QbG10, in table 2, although it does not carry any attached epitope [217,218,219,220,221]. However, this potentially successful vaccine initially originated from epitope-coupling methodology.…”
Section: Vaccines and Vaccine Candidatesmentioning
confidence: 99%
“…It has been demonstrated that MS2 VLPs can be conjugated to peptides recognizing human hepatocellular carcinoma cells and can be loaded with vastly different types of cargo, including low molecular weight chemotherapeutic drugs, siRNA cocktails, protein toxins and nanoparticles, resulting in the selective killing of target cells [268]. The packaging of Qβ VLPs with immunostimulatory CpG sequences led not only to the development of potential allergy vaccines (see above) but also strongly contributed to the general understanding of the mechanics of oligodeoxynucleotide-induced stimulation [217,218,219,220,221,222,223,224,225,226,227,228,229,269,270]. …”
Section: Nonvaccine Applicationsmentioning
confidence: 99%